2001
DOI: 10.1021/ma0103831
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cap Separation in Nitroxide-Regulated “Living” Free Radical Polymerization:  Application of a Novel Methodology Involving a Prefluorescent Nitroxide Switch

Abstract: A novel approach employing a prefluorescent paramagnetic sensor has been employed to determine the absolute kinetics for end-cap cleavage in TEMPO-capped polystyrene obtained by "living" free radical polymerization. This new methodology takes advantage of the suppression of coumarin fluorescence when this chromophore is tethered to a paramagnetic nitroxide. This coumarin-nitroxide is an excellent free radical trap for carbon-centered radicals; upon radical trapping, the resulting diamagnetic alkoxyamine is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…However, the use of this approach has expanded widely and now includes applications in the biological and health sciences (eg., Pou et al, 1993;Kalai et al, 1998;Hideg et al, 1998;Li et al, 1999a, 1999b, Lozinsky et al, 2001, Flicker and Green, 2001, Haugland, 2001) and polymer chemistry (eg., Gerlock et al, 1993;Moad et al, 1999;Ballesteros et al, 2001).…”
Section: Transitionsmentioning
confidence: 99%
“…However, the use of this approach has expanded widely and now includes applications in the biological and health sciences (eg., Pou et al, 1993;Kalai et al, 1998;Hideg et al, 1998;Li et al, 1999a, 1999b, Lozinsky et al, 2001, Flicker and Green, 2001, Haugland, 2001) and polymer chemistry (eg., Gerlock et al, 1993;Moad et al, 1999;Ballesteros et al, 2001).…”
Section: Transitionsmentioning
confidence: 99%
“…Blough and co-workers have shown that these covalently-linked nitroxidefluorophore adducts can be employed as very sensitive optical sensors of radical/redox reactions (8-11). Scaiano and co-workers have also developed a number of prefluorescent probes allowing radical and/or antioxidant detection in homogeneous and heterogeneous systems (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Blough and co-workers have shown that these covalently-linked nitroxidefluorophore adducts can be employed as very sensitive optical sensors of radical/redox reactions (8-11). Scaiano and co-workers have also developed a number of prefluorescent probes allowing radical and/or antioxidant detection in homogeneous and heterogeneous systems (12)(13)(14).However, there is no report of studies on the interaction between nitroxides radicals and conjugated polyelectrolytes until now and the mechanism is also not clear. In an effort to construct highly sensitive optical probes of radical/redox species, we sought to exploit both the radical trapping and fluorescence quenching properties of the nitroxides by constructing a system that contains nitroxides and conjugated polyelectrolytes.…”
mentioning
confidence: 99%
“…The high degree of compatibility with a wide range of functional monomers and good tolerance of water and oxygen in the systems make RAFT technique has been widely used in the synthesis of functional polymers. For example, coumarin and its derivatives have been successfully grafted onto the chain of polymer by living free radical polymerization [45,46]. In this work, we report a method for the fabrication of photo-and thermal-sensitive superhydrophobic surface by the combination of RAFT and click chemistry, resulting in that the block polymers are grafted onto the surface of silica nanosphere.…”
mentioning
confidence: 99%